(untitled) (Bodhi Path, 2021)
Mental illnesses are not the outcome of modern lifestyle; it has been present since time immemorial. In this paper, we present a case study from Buddha’s lifetime, the story of Patacara, her mental illness and her recovery from it after following Buddha’s mindfulness meditation. We further compare the information available through the modern neuroscientific methods, specifically the DSM criteria for the diagnosis of schizophrenia spectrum and other psychotic disorders. Finally, we reviewed the clinical trials focussed on the intervention of psychosis/schizophrenia using mindful meditations.